Pengembangan Kapasitas SDM UMKM Emping Jagung sebagai Upaya Meningkatkan Daya Saing Produk Lokal di Desa Banyu Urip - Rangga, Rangga; Fitriasuri; Heriyanto; Mukran (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Corn chip MSMEs (Micro, Small, and Medium Enterprises) in Banyu Urip Village have untapped economic potential due to limitations in technology, management, and marketing strategies. This study aims to develop the human resource capacity of corn chip MSMEs through community-based mentoring to enhance the competitiveness of local products. The method used is participatory qualitative, involving field observation, interviews, training, and direct mentoring integrated with courses on MSME Empowerment & Village Digitalization, Technology Application, as well as Leadership and Community Communication. The results indicate a significant improvement in the capacity of MSME actors in business management, product innovation (taste diversification), packaging design using digital applications (Canva), and basic understanding of digital marketing. The application of appropriate technology increased production efficiency, while the participatory approach and collaborative leadership strengthened institutional capacity and business sustainability. It is concluded that holistic and contextual human resource development can drive the transformation of traditional MSMEs into more competitive and digitally adaptive businesses.